CO2 Emission Inventory of on road vehicles in Selangor State Inpeninsular Malaysia - Ghadimzadeh, Azadeh; Ahmad Makmom, Abdullah; Chng, John Loi Kok; Askari, Arameh; Narany, Tahoora Sheikhy; Mohd Asrul, Jamalani; Elhadi, Rasheida E.; Gumel, Danladi Yusuf; Fallah, Marzieh (RS Publication, 2015)
The transportation sector has greatly contributed to the socio-economic development with inherent environmental impacts. This study estimated the emission of CO2 from transportation sector, particularly from the use of passenger cars in Selangor Malaysia. The total CO2 emission from the region was calculated based on total fuel consumption (Kg) and Emission Factor of CO2 (gr/kg fuel). Lorries and cars were responsible for the highest CO2 emission and the emissions rate were directly related to the type and amount of fuel used and emission factor of fuel. High amount of CO2 emission was due to increase in vehicles on the road thereby increasing pollution on the environment. GIS is one of the most suitable methods to estimate the total CO2 emission and the split between different vehicle types as it determined by the kilometre covered for each vehicle category.